PENGARUH PEMANFAATAN MULTIMEDIA UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SISTEM EKSKRESI MANUSIA DI KELAS XI TAMAN MADYA (SMA) TAMANSISWA PEMATANGSIANTAR - Suryati Napitupulu, Kristina; Rosenta Purba, Ika; Rajagukguk, Salome (Jurnal Metabio, 2023)
This study aims to determine the effect of multimedia utilization on improving student learning outcomes on the human excretory system and the magnitude of the impact of multimedia utilization on improving student learning outcomes on the excretory system in grade XI Taman Madya (SMA) Tamansiswa Pematangsiantar. The population in this study was 64 students consisting of two classes. The sample was taken by random assignment, i.e., the population size was equal to the sample size. This resulted in two classes: a control class (XI-1) with 32 students and an experimental class (XI-5) with 32 students. Thus, the sample size was 64 students. The control class was treated using conventional methods, while the experimental class was treated using PowerPoint multimedia. Data analysis was performed by finding the mean (X̅ ), standard deviation (S), and hypothesis testing (t-test) at a significance level of α = 0.05. The results obtained an average post-test score of 88 for the control class and 90.12 for the experimental class, with a difference in learning outcomes of 2.12. From the results of the hypothesis testing (t-test), the calculated t (2.790) > t table (1.99) at a significance level of α = 0.05 and degrees of freedom (dk) = 62, so Ho is rejected and Ha is accepted, meaning there is an influence of multimedia utilization to improve student learning outcomes on the human excretory system material in class XI Taman Madya (SMA) Tamansiswa Pematangsiantar. It is concluded that there is an influence of multimedia utilization to improve student learning outcomes on the human excretory system material in class XI Taman Madya (SMA) Tamansiswa Pematangsiantar.